Hubungan Pemilihan Jajanan Sehat dalam Mengembangkan Perilaku Hidup Sehat pada Siswa Kelas IV Sekolah Dasar - Dida Anjani; Pupung Rahayu Noviati; Mamat Rohimat (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2021)
Snacks are one type of food that is often consumed by school children. Given the important role of snacks for children, this research was conducted with the aim of knowing the relationship between choosing healthy snacks in developing healthy lifestyle behaviors in fourth grade elementary school students. The method used in this research is descriptive research. The population and research sample were all fourth grade students at SDN Talun in the 2021 academic year. The instrument used in this study was a questionnaire test sheet. Student test results are processed using the rank correlation test. Based on the results of data analysis using the rank correlation test, the value of p = 0.27, which is greater than 0.05. Thus Ho is accepted, this means that there is no relationship between knowledge about street food and children's behavior in choosing food.